Civilian Nuclear Power : Economic Issues and Policy Formation - Mullenbach, Philip (Twentieth Century Fund, 1963)
"Civilian Nuclear Power" presenta una serie de estudios sobre aspectos políticos y económicos de los usos de la energía nuclear en los Estados Unidos de América. Contiene los siguientes temas generales: Reactor Technology and Economic Policies; U.S. Need for Nuclear Power; U.S. Program Resources; Economic Policies; Foreign Need: The Strategic Economic Factor; Foreign Programs and Resources; Nuclear Power and Foreign Policy; Prospects for Foreign Exchange Savings: Western Europe and Japan; The Soviet Nuclear Power Program.